(untitled) (Docentes 2.0 Journal, 2025)
The COVID-19 pandemic generated changes in the traditional way of imparting knowledge in educational institutions, leading them to modify their planning and migrate to virtual spaces. The general objective of the research was to identify the reflections on the perceptions of teachers from the Faculty of Engineering of a private Peruvian university about their digital skills during the pandemic. The research was based on a phenomenological paradigm, a hermeneutic method, and a qualitative interpretive and cross-sectional approach. This allowed us to understand teachers’ perceptions and explore the meaning of the transition process from face-to-face to digital. The sample consisted of 11 teachers, to whom a semi-structured interview of 33 questions of our elaboration was applied based on the European DigCompEdu framework. For data collection, semi-structured interviews and a sociodemographic form were used. The analysis of the results was based on a thematic approach, highlighting the teachers’ reflections on their level of digital skills. The findings indicate that although teachers faced significant challenges when migrating to the virtual environment, many experienced progress in their digital skills. The discussion raised the idea that institutional training and collaborative work are key to improving digital skills. However, limitations related to workload and time available for training were also highlighted. In conclusion, the need for educational policies that promote continuous training adapted to the technological needs of the current educational context is underlined.